Prevalence of Gastrointestinal Side Effects in Pediatric Azithromycin Users Between 2019 and 2021: a retrospective study - José R. SANTOS-NETO; Mirla F. BORGES; Isabella R. DESTEFANI; Natalia B. PINTO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To verify the prevalence of gastrointestinal side effects in patients who used azithromycin between 2019 and 2021. Methodology: This study has a quantitative, retrospective character, using data from 200 patient records between 2019 and 2021. Inclusion criteria were patients who were hospitalized or admitted to the emergency department without any gastrointestinal complaints and who during hospitalization used azithromycin both alone and in conjunction with other antibiotics, regardless of gender. Exclusion criteria were: patients who arrived at the emergency room or outpatient clinic reporting gastrointestinal symptoms, but who did not use macrolides; patients with previous gastrointestinal inflammatory diseases, as it can cause a confounding factor in the inferential analysis. Results: the prevalence found was 24.5%; the most reported side effects were: diarrhea (39.6%), constipation (29.2%), bloating (12.5%), vomiting (10.4%), abdominal pain (8.3%); the Odds Ratio (OR) of length of stay in days and dosage were 1.23 (95% CI 1.06 to 1.42) and 1.001 (95% CI 1.0008 to 1.002), respectively. Conclusion: The high prevalence of side effects and the associations evaluated show the importance of efficient care in order to reduce them.